Evaluating [68Ga]Ga-p14-032 as a Novel PET Tracer for Diagnosis Cerebral Amyloid Angiopathy - Zhang, Qihui; Zhao, Xiaobin; Lei, Peng; Kung, Hank F.; Yang, Zhi; Zhu, Lin; Wang, Shujing; Zhu, Hua; Meng, Xiangxi; Duan, Yunyun; Sun, Li; Pan, Jianwei; et al. (Frontiers in Neurology, 2021)
Objective: We aimed to investigate the distribution of [68Ga]Ga-P14-032, a novel PET ligand that binds to vascular amyloid, in patients diagnosed clinically with probable cerebral amyloid angiopathy (CAA), compared to patients with Alzheimer’s disease (AD) and normal controls (NC). Methods: This longitudinal cohort study was composed of 10 subjects (3 probable CAA patients, 2 AD patients, 5 NC subjects), recruited from clinic in China. CAA patients had a history of lobar intracerebral hemorrhage (ICH) and met modified Boston criteria for probable CAA. All participants were aged at least 55 years and underwent [68Ga] Ga-P14-032 PET/CT or/and PET/MRI, and the Montreal Cognitive Assessment (MoCA) on initial assessment. Demographics were measured at baseline (diabetes, hypertension, hypercholesterolemia, ischemic stroke and ICH). Two PET imaging experts reviewed the PET images with cortical standardized uptake value ratio (SUVr) displayed on a color scale and visually classified the images as positive or negative. The mean of SUVr was calculated using the pons as reference. Results: In CAA patients, PET scans were positive in regions with higher numbers of CMBs. No significant signal was seen in AD subjects or controls. The relative [68Ga]Ga-P14-032 retention in the cortex was stronger in patients with CAA than AD and NC (median SUVr 2.68±1.53 versus 1.77±0.08 and 0.83±0.24). Conclusions: Our results provide early evidence that the [68Ga] Ga-P14-032 PET probe binds preferentially to vascular amyloid, and may be a useful tracer for diagnosing CAA.